2011
DOI: 10.4103/0972-0707.80734
|View full text |Cite
|
Sign up to set email alerts
|

An evalution of compressive strength of newer nanocomposite: An in vitro study

Abstract: Aim:The purpose of the study is to assess and compare compressive strength of newer nanocomposites (FiltekZ350, Ceram X Mono, Ceram X Duo) with microhybrid (Tetric Ceram) and to compare difference in compressive strength of newer nanocomposites.Materials and Methods:Forty eight specimens of composite were fabricated using customized biparpite brass mold measuring 5mm x 5mm and were grouped with twelve specimens in each Group I : Tetric Ceram, Group II: Filtek Z 350, Group III : Ceram X Mono, Group IV : Ceram X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Incorporated nanofillers in adhesives compositions increased resistance against fracture and wear, provided higher dimensional stability and produced higher SBS than conventional adhesives 20 . Other studies reported comparable 21 , 22 or lower but still acceptable shear bond strength, 23 , 24 when nanofilled adhesives were used for bonding orthodontic brackets.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporated nanofillers in adhesives compositions increased resistance against fracture and wear, provided higher dimensional stability and produced higher SBS than conventional adhesives 20 . Other studies reported comparable 21 , 22 or lower but still acceptable shear bond strength, 23 , 24 when nanofilled adhesives were used for bonding orthodontic brackets.…”
Section: Discussionmentioning
confidence: 99%
“…This combination reduces the interstitial spacing of the filler particles, thus increasing filler loading. [ 16 ] This is reflected in their higher fracture toughness. The high-viscosity bulk-fill nanocomposite; in addition to having the above-mentioned properties of a nanocomposite, is said to contain two novel methacrylate monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Nano-particles in CD contain methacrylic group linked to polysiloxane backbone. 22 Siloxanes, which are chemically similar to glass and ceramic, increase bond strengths. In the present study, combination with CD composite resin showed the highest bond strength (16.2 ± 4.2MPa) in the composite resin groups.…”
Section: Discussionmentioning
confidence: 99%